Social media utilization and knowledge levels in exclusive breastfeeding among mothers in Indonesia - Deswani Deswani; Dea Eki Rahmawati; Yuli Mulyanti; Syafdewiyani Syafdewiyani; Rita Ismail; Sri Djuwitaningsih (PAGEPress Publications, 2023)
The utilization of social media for obtaining information on exclusive breastfeeding is driven by various user-friendly features that facilitate information retrieval. This study delves into understanding the correlation between mothers' engagement with social media for information and their knowledge levels regarding exclusive breastfeeding in Indonesia. Through a cross-sectional analysis involving 93 purposefully selected respondents, demographic factors such as age, education, occupation, social media usage for breastfeeding information, and knowledge levels were evaluated using a validated questionnaire. Descriptive analysis was applied to the data, and significance testing was conducted using Chi-square tests. The questionnaire underwent validity and reliability tests, confirming its robustness. Results indicated a significant association (p < 0.000) between social media usage for breastfeeding information and the knowledge levels of mothers successfully practicing exclusive breastfeeding. Mothers who achieved exclusive breastfeeding demonstrated a discernible level of knowledge about utilizing social media as an information source for breastfeeding. This study highlights the escalating role of social media in shaping mothers' understanding of exclusive breastfeeding. The findings underscore the significance of targeted interventions and educational programs through social media platforms to enhance breastfeeding practices.